Cyclic Nucleotide-Gated Ion Channel 6 Mediates Thermotolerance in Arabidopsis Seedlings by Regulating Hydrogen Peroxide Production via Cytosolic Calcium Ions - Wang, Wenxu; Zhang, Jiaojiao; Ai, Lijuan; Wu, Dan; Li, Bing; Zhang, Lingang; Zhao, Liqun (Frontiers in Plant Science, 2021)
We previously reported the involvement of cyclic nucleotide-gated ion channel 6 (CNGC6) and hydrogen peroxide (H2O2) in the responses of plants to heat shock (HS) exposure. To elucidate their relationship with plant thermotolerance, we examined the effects of HS on several groups of Arabidopsis (Arabidopsis thaliana) seedlings: wild type, cngc6, and its complementation line. After HS exposure, the level of H2O2 was lower in the cngc6 seedlings than in the wild-type seedlings but significantly increased in the complementation line. The treatment of seeds with calcium ions (Ca2+) increased the H2O2 levels in Arabidopsis seedlings under HS conditions, whereas treatment with EGTA (a Ca2+ chelator) inhibited it, indicating that CNGC6 may stimulate the accumulation of H2O2 in a manner dependent on an increase in cytosolic Ca2+ ([Ca2+]cyt). This was verified by phenotypic observations and thermotolerance testing with transgenic plants overexpressing AtRbohB and AtRbohD (two genes involved in HS-responsive H2O2 production), respectively, in a cngc6 background. Real-time reverse transcription-polymerase chain reactions and western blotting indicated that CNGC6 stimulated the gene transcription of HS factors and the accumulation of HS proteins via H2O2. These data indicate that CNGC6 acts upstream of H2O2 in the HS pathway, increasing our understanding of the initiation of plant responses to high temperatures.